Kinetika Adsorpsi Pada Penjerapan Ion Timbal Pb2+ Terlarut Dalam Air Menggunakan Partikel Tricalcium Phosphate - Maihendra, Maihendra; Fadli, Ahmad; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One of the heavy metals can pollute the water is metal ion of Pb2+. Concentration of ions Pb2+ can be removed by adsorption method. The purposes of tihis research are to observe the effect of temperature and adsorbent dosage on the adsorption of metal ion Pb2+ using tricalcium phosphate (TCP) adsorben and determine a suitable adsorption kinetic model. Five hundred mililiter Pb2+ solution with of 3mg/L were added 0,5 gr, 1 gr and 1,5 gr of TCP in a glass beaker and stirred with rate of 300 rpm at a temperature of 30 oC. Pb solution was taken at a certain time, the solution centrifuged and supernatant analyzed by AAS. The result Showed that rate of adsorption increased with temperature and adsorbent dosage. Minimum constant value of adsorption kinetic of adsorption kinetic was 1,720 g/mg.min obtained at temperature 30oC and adsorbent dosage 0,5 gr. Where as maximun value adsorption kinetic constant 8,479 g/mg.min obtained at temperature 30oC adsorbent dosage 1,5 gr. The appropiate model for kinetic followed pseudo second order.Keyword : Adsorption, Kinetic, Lead (Pb2+), Tricalcium phosphate